Traffic noise changes due to water on porous and dense asphalt surfaces - Freitas, Elisabete F. (2009)
The standards for the environmental quality required by the European Community are very demanding in what concerns traffic noise. The interaction tire/road is undoubtedly one of the main sources of traffic noise. Nevertheless, standards do not account for the increase in the noise level caused by rain falling onto road surfaces. Therefore, the aim of this work is to study the effects of water on pass-by noise since the weather is rainy about 25 per cent of the year in Portugal. Thus, it addresses two currently used pavement surfaces, porous asphalt and dense asphalt, constructed in a motorway. A version of the Statistical Pass-By Method was used to assess noise levels with dry and wet surfaces, using a selected set of heavy and light vehicles. The results include analysis of the statistical pass-by index, pressure noise levels and noise spectrum. Noise levels increase significantly with the presence of water, shifting the overall noise by 4 dB(A). The benefits of porous asphalt are null for heavy vehicles, particularly at high speeds. CE Database subject headings: traffic noise, water, porous asphalt, dense asphalt, statistical pass-by method, noise level, noise spectrum.